2021
DOI: 10.3389/fimmu.2021.647824
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and Dendritic Cells Are Not the Major Source of Pro-Inflammatory Cytokines Upon SARS-CoV-2 Infection

Abstract: The exact role of innate immune cells upon infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and their contribution to the formation of the corona virus-induced disease (COVID)-19 associated cytokine storm is not yet fully understood. We show that human in vitro differentiated myeloid dendritic cells (mDC) as well as M1 and M2 macrophages are susceptible to infection with SARS-CoV-2 but are not productively infected. Furthermore, infected mDC, M1-, and M2 macrophages show only slight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
45
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 52 publications
12
45
4
Order By: Relevance
“…Arguably, ex vivo cultures of primary macrophages, albeit valuable, have a limited lifespan which can affect cell polarization and transcriptional responses after extended periods of culture. Nevertheless, our findings are aligned with reports that macrophages are unlikely to drive the initial wave of pro-inflammatory cytokines upon SARS-CoV-2 infection [29,31]. In addition, the substantial increase in induction of proinflammatory cytokines upon IFNstimulation suggests that macrophages may participate in secondary or ensuing waves of inflammatory responses leading to ARDS in severe COVID-19 patients.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Arguably, ex vivo cultures of primary macrophages, albeit valuable, have a limited lifespan which can affect cell polarization and transcriptional responses after extended periods of culture. Nevertheless, our findings are aligned with reports that macrophages are unlikely to drive the initial wave of pro-inflammatory cytokines upon SARS-CoV-2 infection [29,31]. In addition, the substantial increase in induction of proinflammatory cytokines upon IFNstimulation suggests that macrophages may participate in secondary or ensuing waves of inflammatory responses leading to ARDS in severe COVID-19 patients.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast Caco-2, Vero E6 and Calu-3 cell lines produced high viral loads (4 × 10 5 -5.5 × 10 5 TCID 50 / mL ) (Figure 1A). Together these findings indicate that macrophages do not support SARS-CoV-2 replication in line with other reports [28][29][30][31]. In contrast, the influenza M gene was detected in cell lysates at 6 hpi, more so in 6:2 Eng/09 infected macrophages (Figure S2).…”
Section: Macrophages Are Refractory To Sars-cov-2 Infectionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, the relative number of CD14++ CD16+ monocytes comprised up to 45% of all monocytes. By comparison, other studies by Niles et al [19] showed that myeloid dendritic cells (mDCs), and neither M1 pro-inflammatory macrophages nor M2 anti-inflammatory macrophages, were stimulated to produce pro-inflammatory cytokines in SARS-COV-2 infection. Many differences have also been described between the severe course of COVID-19 and typical MAS.…”
Section: Introductionmentioning
confidence: 77%